Computed tomography-derived cardiovascular risk markers, incident cardiovascular events, and all-cause mortality in nondiabetics: the Multi-Ethnic Study of Atherosclerosis. (October 2014) - Yeboah, Joseph; Carr, J Jeffery; Terry, James G; Ding, Jingzhong; Zeb, Irfan; Liu, Songtao; Nasir, Khurram; Post, Wendy; Blumenthal, Roger S; Budoff, Matthew J
Aim: We assess the improvement in discrimination afforded by the addition of the computed tomography risk markers thoracic aorta calcium (TAC), aortic valve calcification (AVC), mitral annular calcification (MAC), pericardial adipose tissue volume (PAT), and liver attenuation (LA) to the Framingham risk score (FRS) + coronary artery calcium (CAC) for incident coronary heart disease (CHD) and incident cerebrovascular disease (CVD) in a multiethnic cohort. Methods and results: A total of 5745 participants were enrolled, with 2710 at intermediate Framingham risk, 210 CVD events, and 155 CHD events). Over 9 years of follow up, 251 had adjudicated CHD, 346 had CVD events, and 321 died. The data were analysed using Cox proportional hazard, receiver operator curve (ROC), and net reclassification improvement (NRI) analyses. In the whole cohort and also when the analysis was restricted to only the intermediate-risk participants, CAC, TAC, AVC, and MAC were all significantly associated with incident CVD, incident CHD, and mortality, and CAC had the strongest association. When added to the FRS, CAC had the highest area under the curve (AUC) for the prediction of incident CVD and incident CHD; LA had the least. The addition of TAC, AVC, MAC, PAT, and LA to FRS + CAC all resulted in a significant reduction in AUC for incident CHD (0.712 vs. 0.646, 0.655, 0.652, 0.648, and 0.569; all p  < 0.01, respectively) in participants with intermediate FRS. The addition of CAC to FRS resulted in an NRI of 0.547 for incident CHD in the intermediate-risk group. The NRI when TAC, AVC, MAC, PAT, and LA were added to FRS + CAC were 0.024, 0.026, 0.019, 0.012, and 0.012, respectively, for incident CHD in the intermediate-risk group. Similar results were obtained for incident CVD in the intermediate-risk group and also when the whole cohort was used instead of the intermediate FRS group. Conclusions: The addition of CAC to the FRS provides superior discrimination especially in intermediate-risk individuals compared with the addition of TAC, AVC, MAC, PAT, or LA for incident CVD and incident CHD. Compared with FRS + CAC, the addition of TAC, AVC, MAC, PAT, or LA individually to FRS + CAC worsens the discrimination for incident CVD and incident CHD. These risk markers are unlikely to be useful for improving cardiovascular risk prediction.